Effect of Ionic Correlations on the Surface Forces in Thin Liquid Films: Influence of Multivalent Coions and Extended Theory - Danov, Krassimir D. (Materials (Basel), 2016)
Experimental data for the disjoining pressure of foam films stabilized by anionic surfactant in the presence of 1:1, 1:2, 1:3, and 2:2 electrolytes: NaCl, Na(2)SO(4), Na(3)Citrate, and MgSO(4) are reported. The disjoining pressure predicted by the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory coincides with the experimental data in the case of a 1:1 electrolyte, but it is considerably greater than the measured pressure in all other cases. The theory is extended to account for the effects of ionic correlations and finite ionic radii. Original analytical expressions are derived for the local activity coefficient, electrostatic disjoining pressure, and asymptotic screening parameter. With the same parameter of counterion binding as for a 1:1 electrolyte, the curves predicted by the extended theory are in perfect agreement with the experimental data for 1:2 and 1:3 electrolytes. In comparison with the DLVO theory, the effect of ionic correlations leads to more effective screening of electrostatic interactions, and lower electric potential and counterion concentrations in the film’s midplane, resulting in lower disjoining pressure, as experimentally observed. The developed theory is applicable to both multivalent coions and multivalent counterions. Its application could remove some discrepancies between theory and experiment observed in studies with liquid films from electrolyte solutions.